The possibility of reclamation criteria success in Indonesia: soil condition, vegetation structure and species composition - Tedi Yunanto; Farisatul Amanah; Nabila Putri Wisnu (Journal of Degraded and Mining Lands Management, 2021)
There are two regulations for mine reclamation success in the forestry area in Indonesia, namely Minister of Forestry Regulation No. P.60/Menhut-II/2009 and Minister of Energy and Mineral Resources Decree No. 1827.K/30/MEM/2018. Both regulations rule vegetation and soil success. This study aims to analyse criteria parameters from both regulations in the mine reclamation and compare them to the surrounding secondary natural forest (SNF). This study was conducted in 6 six types of mine reclamation stand structures: 1, 4, 6, 9, 11-year-old plantation and SNF using 1 hectare of the circular plot each (total 6 ha). Soil samples were collected from 40 cm depth to analyse physical, biological and chemical conditions. Mine reclamation areas had almost similar physical, biological and chemical soil conditions with SNF. Nevertheless, due to the potential acid-forming (PAF) material from overburden, the 1-year-old plantation had pH = 3.23-3.27. The highest diversity index and the number of species and families in all reclamation areas were H’ = 1.82 (11-year-old); 14 species (9-year-old); and 11 families (9-year-old), comparing with SNF were H’ = 3.48; 67 species, and 31 families. Conversely, vegetation structure parameters in mine reclamation areas were higher than SNF (diameter at height breast (DBH; 1.3 m) = 28.42 cm; tree density = 469/ha; basal area = 35.04 m2/ha; and total height = 16.85 m). Compared to the SNF, vegetation structure and soil conditions are mostly possible for mine reclamation success. Still, species composition needs to be considered further as a standard interval to meet the criteria.